The Prospective Two-Dimensional Graphene Nanosheets: Preparation, Functionalization and Applications - Yang, Zhi; Gao, Rungang; Hu, Nantao; Chai, Jing; Cheng, Yingwu; Zhang, Liying; Wei, Hao; Kong, Eric Siu-Wai; Zhang, Yafei (Nano-Micro Letters, 2012)
Graphene, as an intermediate phase between fullerene and carbon nanotube, has aroused much interests among the scientific community due to its outstanding electronic, mechanical, and thermal properties. With excellent electrical conductivity of 6000 S/cm, which is independent on chirality, graphene is a promising material for high-performance nanoelectronics, transparent conductor, as well as polymer composites. On account of its Young’s Modulus of 1 TPa and ultimate strength of 130 GPa, isolated graphene sheet is considered to be among the strongest materials ever measured. Comparable with the single-walled carbon nanotube bundle, graphene has a thermal conductivity of 5000 W/(m·K), which suggests a potential application of graphene in polymer matrix for improving thermal properties of the graphene/polymer composite. Furthermore, graphene exhibits a very high surface area, up to a value of 2630 m2/g. All of these outstanding properties suggest a wide application for this nanometer-thick, two-dimensional carbon material. This review article presents an overview of the significant advancement in graphene research: preparation, functionalization as well as the properties of graphene will be discussed. In addition, the feasibility and potential applications of graphene in areas, such as sensors, nanoelectronics and nanocomposites materials, will also be reviewed.